Program Kegiatan KKN Kelompok Feb.Hukum,Farmasi,Fkip/Bahasa Inggris Di Desa Pematang Rambai Kecamatan Nibung Hangus Kabupaten Batu Bara - Chairil Wahyukrisna D; Hadi Halomoan Hasibuan; Wulan Novita Sari; Rusni Harianti Nainggolan; Natasya; Arief Hadian; Sugiar (LPPI UMN AL WASHLIYAH, 2026)
The Community Service Program (KKN) in Pematang Rambai Village, Batu Bara Regency, conducted by interdisciplinary students from Universitas Muslim Nusantara Al-Washliyah Medan, focused on community empowerment. Through methods of surveys, outreach, and training over 20 days, this program aimed to implement the Tri Dharma of Higher Education. Key activities included innovating local MSME (Micro, Small, and Medium Enterprises) products, raising awareness about stunting prevention at integrated health posts (posyandu), providing creative English education for children, creating village signposts, and conducting a dish soap making workshop. The results demonstrated a significant increase in the community's knowledge and skills, ranging from MSME management to health awareness. Additionally, children's motivation to learn increased, and village administration became more informative. Overall, this KKN successfully enhanced the residents' self-reliance, welfare, and quality of life, while also affirming the role of students as agents of social change who make a tangible contribution to the village's progress.